Prevalence of hypothyroidism in infertile women and evaluation of response of treatment for hypothyroidism on infertility - Verma, Indu (Medknow Publications & Media Pvt Ltd, 2012)
CONTEXT: Prevalence of hypothyroidism is 2–4% in women in the reproductive age group. Hypothyroidism can affect fertility due to anovulatory cycles, luteal phase defects, hyperprolactinemia, and sex hormone imbalance. AIMS AND OBJECTIVES: To study the prevalence of clinical/sub-clinical hypothyroidism in infertile women and the response of treatment for hypothyroidism on infertility. MATERIALS AND METHODS: A total of 394 infertile women visiting the infertility clinic for the first time were investigated for thyroid stimulating hormone (TSH) and prolactin (PRL). Infertile women with hypothyroidism alone or with associated hyperprolactinemia were given treatment for hypothyroidism with thyroxine 25–150 μg. RESULTS: Of 394 infertile women, 23.9% were hypothyroid (TSH > 4.2 μIU/ml). After treatment for hypothyroidism, 76.6% of infertile women conceived within 6 weeks to 1 year. Infertile women with both hypothyroidism and hyperprolactinemia also responded to treatment and their PRL levels returned to normal. CONCLUSION: Measurement of TSH and PRL should be done at early stage of infertility check up rather than straight away going for more costly tests or invasive procedures. Simple, oral hypothyroidism treatment for 3 months to 1 year can be of great benefit to conceive in otherwise asymptomatic infertile women.